Edible Coating Pati Jagung dengan Penambahan Ekstrak Jahe Merah untuk Memperpanjang Umur Simpan Tomat (Lycopersicum esculentum) - Putri, Desi Septia; Harun, Noviar; Efendi, Raswen; Dewi, Yossie Kharisma (Agriculture Faculty, 2024)
This research aims to obtain the best addition of red ginger extract in corn starch edible coating to extend the shelf life of tomatoes. This research method used an experimental method, obtaining 15 experimental units by using a fully randomized design (CRD) with five treatments and three replications. The treatments used include P0 (without addition of red ginger extract), P1 (1% addition of red ginger extract), P2 (3% addition of red ginger extract), P3 (5% addition of red ginger extract), and P4 (7% addition of red ginger extract) in edible coating of corn starch with addition red ginger extract to extend shelf life tomatoes and stored for 21 days. The results showed that the addition of red ginger extract affected weight loss, hardness, total dissolved solids, pH, vitamin C and total microbes. Data were analyzed statistically using analysis of variance (ANOVA) and continued with DMRT at 5% level. The best treatment of this research was P4 with a 14.71% weight loss value, 5.58 kgf hardness, 1.413Brix total dissolved solids, 4.92 pH, 27.41 mg/100g vitamin C and 4.46 log CFU/g total microbes.